Analysis of pediatric subdural empyema outcome in relation to computerized tomography brain scan - Md. Ralib@Md. Raghib, Ahmad Razali; Mohd Ariff, Abdul Rahman; Shuaib, Ibrahim Lutfi; Naing, Nyi Nyi; George, P Jain; Abdullah, Jafri Malin (Faculty of Tropical Medicine, Mahidol University, 2004)
A cross-sectional study was conducted to predict the outcome in patients with subdural empyema, using initial and post-treatment CT scan brain parameters. Data collection was done on those children who were diagnosed to have subdural empyema by CT scan of the brain with contrast, who underwent burrhole evacuation, from February 2000 until April 2002. Numerous factors, such as coma or loss of unconsciousness at diagnosis, age, types of antibiotic, microbiology, extension of empyema, associated cerebral infarction and ventriculitis, were analyzed. Poor prognosis was associated with loss of consciousness, and hypodensity by CT scan at presentation (p < 0.005). Patients with an extensive subdural empyema will have a good outcome if they are treated early and aggressively with antibiotics and burrhole evacuation.